0423 Associations of individual behaviors and ambient factors in the sleep environment with nighttime sleep parameters in pregnant women with insomnia. (25th May 2022) - Badon, Sylvia; Manber, Rachel; Simpson, Norah
Abstract: Introduction: Sleep hygiene and environment are important for adequate sleep quantity and quality. We examined two aspects of the sleep environment, individual behaviors and ambient factors, with nighttime sleep parameters in pregnant women with insomnia. Methods: We used baseline data from a randomized controlled trial of insomnia treatment during pregnancy for this cross-sectional analysis (n=70). Women completed a questionnaire assessing whether they regularly engaged in five individual behaviors in bed (yes/no) and how much their sleep was disrupted by seven ambient factors (scale from 1=not very much to 5=very much) and wore an Actiwatch 2 for a subsequent 7-day period. Responses of 4 or 5 for ambient factor items were categorized as ambient factors perceived to disrupt sleep. Generalized estimating equation regression models were used to estimate associations of individuals behaviors and ambient factors perceived to disrupt sleep with actigraphy-measured total nighttime sleep duration and sleep efficiency. Results: The most commonly endorsed individual behaviors were using the internet/computer in bed (64%) and watching television in bed (43%), followed by talking on the phone in bed, listening to music in bed, and playing video/electronic games in bed (16-27%). Watching television in bed was associated with 23 fewer minutes of actigraphy-measured nighttime sleep (95% CI: -44, -1). No individual behavior was associated with actigraphy-measured sleep efficiency (all P>0.05). The most commonly endorsed ambient factors perceived to disrupt sleep were environmental noise (41%) and uncomfortable temperature (37%), followed by movement from others sharing the bed, having to take care of children in the middle of the night, someone else snoring, and light (24-29%). No ambient factors perceived to disrupt sleep were associated with actigraphy-measured nighttime sleep duration or efficiency (all P >0.05). Conclusion: Individual behaviors and ambient factors perceived to disrupt sleep were common in pregnant women with insomnia. In this study, only watching television in bed was associated with objectively-measured nighttime sleep duration. Our findings suggest that future research could investigate potential interfering roles of arousal and cognitive factors contributing to insomnia during pregnancy. Support (If Any): National Institutes of Health (K99HD100585, R01NR013662)